Rapid maxillary expansion as a treatment for obstructive sleep apnea syndrome in children and adolescents: an evaluation by polysomnography and quality of life (Research, Society and Development, 2021)
Sleep-related breathing disorders range from snoring to more serious disorders, such as Obstructive Sleep Apnea Syndrome (OSAS). It affects the quality of life of children and are related to mouth breathing, one of the main causes of malocclusion. The aim of this research was to evaluate the polysomnography respiratory data and quality of life in patients diagnosticated with OSAS before and after rapid maxillary expansion (RME). Children aged 7 to 11 were included, all of them presented respiratory complaints of snoring with or without associated respiratory pauses. Children with genetic and craniofacial syndromes, neuropaths, children with grade 4 tonsils or signs of OSAS severity with cyanosis, pulmonary hypertension or pulmonale were excluded. All children underwent occlusal examination and type 3-night polysomnography, in addition to filling out the OSA 18 quality of life questionnaires and the Sleep Disorders Scale in Children. The data were compared before (T0) and after (T1) RME procedure. For parametric values, paired t test was used, and for the non-parametric ones, the Wilcoxon test was applied. There was a significant variation in AHI from T0 = 6.89 to   T1 = 5.34, as well as a significant reduction in OSA 18 scores in 46.2% of cases. RME was effective for the treatment of OSAS considering polysomnography results and also improved quality of life in children.